BEYOND DISPOSABLES: NAVIGATING ECO-FRIENDLY MENSTRUAL ALTERNATIVES - Professor (Dr.) Sabrina Sareen, (Chelonian Research Foundation, 2024)
The Red Dot Project –Best Practice of Lakshmibai College, sought to shed light on the environmental and health repercussions of single-use sanitary napkins. Through the engagement of Apparel Design students of the college, the project aimed to educate and train underprivileged women in Wazirpur Village. The focus had been on crafting cost-effective and reusable fabric sanitary napkins, fostering both women’s emancipation and environmental conservation. This paper further gives an insight into recent developments in the area of sustainable menstrual initiatives and the progress made so far.